Fabrication of a hierarchical nanoreactor based on COFs for cascade enzyme catalysis. Issue 24 (4th March 2022) - Yang, Xiaolian; Tan, Zheng; Sun, Hanjun; Tong, Yushi; Huang, Xiaochun; Ren, Junying; Wang, Chen; Shen, Weiyang
Abstract : A hierarchical nanoreactor based on covalent organic frameworks was fabricated using polystyrene spheres as a template. When applied in cascade catalysis, the nanoreactor significantly improved the catalytic activity of internal enzymes. Abstract : A hierarchical nanoreactor based on covalent organic frameworks (COFs) was fabricated using polystyrene spheres (PSs) as a template. When applied in cascade catalysis, the nanoreactor significantly improved the catalytic activity of internal enzymes, and showed protection for the enzyme in harsh environments. Moreover, glucose can be sensitively detected (detection sensitivity: 10 μM) by the nanoreactor.